VD_FINDINFO Arrêt / 2010 / 660 vom 5. März 2010 - VD Tribunal cantonal (2010)
AIASSURANCE, RÉVISION DE LA RENTE, RECONSIDÉRATION | 17 al. 1 LPGA, 53 al. 2 LPGA, 87 al. 2 RAI, 88a al. 1 RAI, 88bis al. 2 let. a RAI, 93 al. 1 let. a LPA-VD